The XMM-SERVS survey: new XMM–Newton point-source catalogue for the XMM-LSS field. Issue 2 (25th April 2018) - Chen (陳建廷), C-T J; Brandt, W N; Luo, B; Ranalli, P; Yang, G; Alexander, D M; Bauer, F E; Kelson, D D; Lacy, M; Nyland, K; Tozzi, P; Vito, F; et al.
ABSTRACT: We present an X-ray point-source catalogue from the XMM-Large Scale Structure (XMM-LSS) survey region, one of the XMM- Spitzer Extragalactic Representative Volume Survey (XMM-SERVS) fields. We target the XMM-LSS region with 1.3 Ms of new XMM–Newton AO-15 observations, transforming the archival X-ray coverage in this region into a 5.3 deg 2 contiguous field with uniform X-ray coverage totaling 2.7 Ms of flare-filtered exposure, with a 46 ks median PN exposure time. We provide an X-ray catalogue of 5242 sources detected in the soft (0.5–2 keV), hard (2–10 keV), and/or full (0.5–10 keV) bands with a 1 per cent expected spurious fraction determined from simulations. A total of 2381 new X-ray sources are detected compared to previous source catalogues in the same area. Our survey has flux limits of 1.7 × 10 −15, 1.3 × 10 −14, and 6.5 × 10 −15 erg cm −2 s −1 over 90 per cent of its area in the soft, hard, and full bands, respectively, which is comparable to those of the XMM-COSMOS survey. We identify multiwavelength counterpart candidates for 99.9 per cent of the X-ray sources, of which 93 per cent are considered as reliable based on their matching likelihood ratios. The reliabilities of these high-likelihood-ratio counterparts are further confirmed to be ≈97 per cent reliable based on deep Chandra coverage over ≈5 per cent of the XMM-LSS region. Results of multiwavelength identifications are also included in the source catalogue, along with basic optical-to-infrared photometry and spectroscopic redshifts from publicly available surveys. We compute photometric redshifts for X-ray sources in 4.5 deg 2 of our field where forced-aperture multiband photometry is available; >70 per cent of the X-ray sources in this subfield have either spectroscopic or high-quality photometric redshifts.